Answer :

petersmwa

Answer:

(2x + 3y) • (4x2 - 6xy + 9y2)

Step-by-step explanation:

Step 1 :

Equation at the end of step 1 :

(8 • (x3)) + 33y3

Step 2 :

Equation at the end of step 2 :

23x3 + 33y3

Step 3 :

Trying to factor as a Sum of Cubes :

3.1 Factoring: 8x3+27y3

Theory : A sum of two perfect cubes, a3 + b3 can be factored into :

(a+b) • (a2-ab+b2)

Proof : (a+b) • (a2-ab+b2) =

a3-a2b+ab2+ba2-b2a+b3 =

a3+(a2b-ba2)+(ab2-b2a)+b3=

a3+0+0+b3=

a3+b3

Check : 8 is the cube of 2

Check : 27 is the cube of 3

Check : x3 is the cube of x1

Check : y3 is the cube of y1

Factorization is :

(2x + 3y) • (4x2 - 6xy + 9y2)

Answer:

8x3−27y3=(2x−3y)(4x2+6xy+9y2)

Step-by-step explanation:

8x^3 - 27y^3=(2x-3y)(4x^2+6xy+9y^2) Use the identity a^3 - b^3 = (a - b)(a^2 + ab + b^2) a=2x b=3y 8x^3 - 27y^3 = (2x - 3y)(4x^2 + 6xy + 9y^2)

Other Questions